2007
DOI: 10.4049/jimmunol.179.5.2999
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB Signaling Regulates Functional Expression of the MHC Class I-Related Neonatal Fc Receptor for IgG via Intronic Binding Sequences

Abstract: The neonatal Fc receptor for IgG (FcRn) functions to transport maternal IgG to a fetus or newborn and to protect IgG from degradation. Although FcRn is expressed in a variety of tissues and cell types, the extent to which FcRn expression is regulated by immunological and inflammatory events remains unknown. Stimulation of intestinal epithelial cell lines, macrophage-like THP-1, and freshly isolated human monocytes with the cytokine TNF-α rapidly up-regulated FcRn gene expression. In addition, the TLR ligands L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
93
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(101 citation statements)
references
References 56 publications
8
93
0
Order By: Relevance
“…Moreover, hypercatabolism of IgG has been observed in mice with lupus-like syndrome, by disease-induced impairment of FcRn function (41). FcRn expression in intestinal epithelial cells, macrophage-like THP-1, and primary human monocytes can be induced by inflammatory markers such as TNF-α and IL-1β (42). Additionally, biodistribution studies with FcRn knockout animals have reported altered PK and distribution of IgG.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, hypercatabolism of IgG has been observed in mice with lupus-like syndrome, by disease-induced impairment of FcRn function (41). FcRn expression in intestinal epithelial cells, macrophage-like THP-1, and primary human monocytes can be induced by inflammatory markers such as TNF-α and IL-1β (42). Additionally, biodistribution studies with FcRn knockout animals have reported altered PK and distribution of IgG.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the expression of the splicing variants is highly regulated by inflammatory cytokines during inflammation, i.e., production of splicing variants of MHC class I molecules can be induced by proinflammatory cytokines [46,47]. Our recent data showed that FcRn expression can be regulated by cytokines such as TNF-α and IL-1β [48]. Taking this into account, it would be interesting to know whether proinflammatory cytokines also regulate or change the patterns of FcRn splicing.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation is differential gene regulation. In this regard, Liu et al (2007) found that stimulation of intestinal epithelial cell lines, macrophage-like THP-1 and freshly isolated human monocytes with TNF-α up-regulated FcRn gene expression. In addition, the TLR ligands LPS and CpG oligodeoxynucleotide enhanced FcRn expression, specifically in THP-1 and monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The FcRn thus seems widely distributed in the human body. It is constitutively expressed, is up-regulated by TNF-α and LPS and down-regulated by IFN-γ (Liu et al, 2007;.…”
Section: Introductionmentioning
confidence: 99%